Bibliometric Analysis of the Thinking Styles in Math and Its' Implication on Science Learning - Sarkingobir, Yusuf; Egbebi, Lukman Femi; Awofala, Adeneye O. A (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The exploration of mathematical thinking styles is a vital area of investigation, particularly concerning its influence on science education within the classroom, given the significant role mathematics plays in advancing scientific understanding. The examination of this subject holds great interest, and its pertinence strongly bolsters prospective teaching and research endeavors. This research aims to perform a bibliometric scrutiny of mathematical thinking styles and their implication on science learning. The focus of this bibliometric inquiry is to elucidate and scrutinize literature congruent with the concept of mathematical thinking styles and their alignment with science learning. The SCOPUS repository is employed as the primary source of document references. Document selection and analysis were conducted using specific keywords in the 'document search' section. Employing diverse document screening methodologies pertinent to mathematical thinking styles and their implication on science learning, a corpus of relevant documents addressing the subject matter was identified. The sequential screening procedures and document findings are discussed comprehensively in this article. Fundamentally, articles pertinent to the bibliometric analysis theme, 'mathematical thinking styles and their implications for science learning,' underscore the significance of delving into students' mathematical thinking styles. Variances in these cognitive styles pose significant challenges for educators' pedagogical approaches in both mathematics and science instruction. This constitutes a pivotal implication of the present study, necessitating educators to adeptly navigate diverse mathematical thinking styles when structuring pedagogy in science and mathematics. Ultimately, this study stands as a pivotal reference for future investigations delving into themes associated with mathematical thinking styles.